The future of medical self-regulation in the United Kingdom – Renegotiating the state–profession bargain?. (December 2014) - Davies, Mark
In April 2014, the Law Commission published its report, Regulation of Health Care Professionals and Regulation of Social Care Professionals in England . This provides a timely reminder that medical regulation remains potentially problematic and contentious. In this article, I review the origins of the so-called state–medical profession bargain created in 1858, the history of its effectiveness, or lack of effectiveness, and the extent to which recent regulatory developments and the Law Commission proposals constitute significant renegotiation of the bargain. I conclude by considering whether the proposal may even represent the beginnings of state imposition of a new bargain, in which other health-care professions might significantly challenge the traditional dominance of doctors.